Toward Green Production of Chewing Gum and Diet: Complete Hydrogenation of Xylose to Xylitol over Ruthenium Composite Catalysts under Mild Conditions - Cai-Juan Liu; Ning-Ning Zhu; Jian-Gong Ma; Peng Cheng (Research, 2019)
Xylitol is one of the most famous chemicals known to people as the essential ingredient of chewing gum and as the sugar alternative for diabetics. Catalytic hydrogenation of biomass-derived xylose with H2 to produce high-value xylitol has been carried out under harsh reaction conditions. Herein, we exhibit the combination of Ru NPs with an environmentally benign MOF (ZIF-67) to afford a heterogeneous composite catalyst. Complete conversion of xylose with 100% selectivity to xylitol was achieved at 50°C and 1 atm H2. This is the first successful attempt to produce xylitol with ambient pressure H2 as well as the first time to achieve a 100% selectivity of xylitol for applicable catalysts. We also proved the universality of the Ru@ZIF-67 towards other hydrogenation processes. Under 1 atm H2, we achieved 100% conversion and >99% selectivity of 1-phenylethanol at 50°C for the hydrogenation of acetophenone. This is also the first report of hydrogenating acetophenone to 1-phenylethanol under 1 atm H2, which confirms that our result not only contributes to enhance the industrial yields of xylitol and reduces both the economical and energy costs but also provides new perspectives on the other hydrogenation process with H2.